The Correlation Between Macrobenthic Mollusk Community Structure, Water Quality, And Sediment For Evaluating The Environmental Status Of The Aquaculture Area In Lake Rawapening - Isman Nasik; Sapto Purnomo Putro; Rully Rahadian; Muhammad Choirul (Jurnal Ilmu Lingkungan, 2025)
Due to the surge in global food demand, aquaculture in Indonesia has expanded rapidly. Fish farming activities using floating net cages that neglect environmental pollution have become a significant issue in Lake Rawapening. Macrobenthic mollusks serve as valuable bioindicators for assessing disturbances in aquatic ecosystems, as they exhibit sedentary behavior, slow movement, and high sensitivity to fluctuations in water quality. This study aims to assess the structure of macrobenthic mollusk communities, environmental quality, and ecological status in the aquaculture areas of Lake Rawapening. Sediment samples were collected from polyculture, monoculture, and reference sites. A total of 9 species from 2 classes and 7 families were found at all three sites, with a low diversity index (H'), indicating limited community stability. Diversity was higher at polyculture sites compared to monoculture sites. Abiotic analysis showed that environmental parameters (temperature, pH, organic carbon, total nitrogen, phosphate) still met quality standards, although dissolved oxygen (DO) levels were low. The sediment substrate was dominated by clayey silt. Temperature was the abiotic factor most strongly correlated with mollusk abundance (r = 0.612; BIO-ENV, PRIMER 6.1.5). Based on the EWS-3 SWJ software, polyculture and monoculture sites were classified as moderately disturbed, while the reference area showed light to moderate disturbance.